Aspek-Aspek Flow Akademik - Nabila Qurrotu Aini; Ilfiandra Ilfiandra; Ipah Saripah (Journal of Innovative Counseling : Theory, Practice, and Research, 2019)
Learning is an important factor for students. The need to learn does not make students able to learn and understand the meaning of learning well. The academic flow could be a support in the learning process of students and students are able to study seriously and live the learning process. Based on the search for various sources, it is known that the aspects of flow consist of absorption by activity and fluency of performance. The results of this study could be used as a reference for students and educators to increase learning success and education quality